Novel S-Scheme β-cu2v2o7/ni/pg-c3n4 Heterojunction Photocatalyst for Sunlight-Induced Degradation of Rhb - Radhalayam, D (Elsevier B.V., 2024)
A novel S-scheme β-Cu2V2O7/Ni/Pg-C3N4 nanocomposite photocatalyst has been advantageously established by propelling β-Cu2V2O7 nanoparticles (NPs) on the top layer of porous graphitic carbon nitride (Pg-C3N4) nanosheets (NSs) using a facile co-precipitation approach. Implementing photoelectrochemical and physicochemical techniques, the crystallinity, purity, optical quality, morphology, chemical composition, and charge separation efficiency of the produced samples were examined. The outcomes indicate that metallic Ni and β-Cu2V2O7 NPs were perfectly encapsulated onto the Pg-C3N4 NSs and well-matched band structures between both semiconductors facilitate the creation of an S-scheme charge transfer path. The fabricated pristine and β-Cu2V2O7/Ni/Pg-C3N4 composite samples were utilized as a catalyst for the removal of rhodamine B (RhB) dye under sunlight irradiation. The β-Cu2V2O7/Ni/Pg-C3N4 nanocomposite exhibits exceptional activity within 60 min of radiation exposure (RhB- 98.56%), whereas β-Cu2V2O7 and Pg-C3N4 show reduced activity (RhB-34.4% and 45.68%). The favourable impact of S-scheme nanocomposite establishment boosted photocatalytic behavior using the intrinsic electric field among Pg-C3N4 NSs and β-Cu2V2O7 and surface plasmon resonance (SPR) effect of metallic Nickel (Ni) NPs for delivering e− and h+ pairs and prolonging the life of charge carriers. According to radical scavenging experiments •O2− is the primary reactive species followed by •OH radicals. The produced nanocomposite has the potential to be employed in large-scale photocatalytic water treatment, as evidenced by the photocatalyst s excellent efficiency and reusability after five consecutive experiments. © 2024 Elsevier B.V.